EFEKTIVITAS CONTEXTUAL TEACHING AND LEARNING (CTL) PADA MATERI PENJUMLAHAN PECAHAN BERPENYEBUT BERBEDA DI KELAS V SD - Varenchi, Theresia; Andika, Refiona; Zainil, Melva; Muhammadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effectiveness of the contextual teaching learning on mathematics learning outcomes in the topic of addition of fractions with different denominators for fifth-grade elementary school students. This research employed a quasi-experimental method with a nonequivalent control group design. The study was conducted at SDN 24 Ujung Gurun in the 2025/2026 academic year. The research sample consisted of class VA as the experimental class with 22 students and class VB as the control class with 23 students. Data were collected through pretest and posttest instruments. Data analysis was conducted using normality tests, homogeneity tests, hypothesis testing with Independent Sample T-Test, and N-Gain tests assisted by IBM SPSS Statistics 30. The results showed that the posttest mean score of the experimental class was 83.64, which was higher than the control class score of 50.65. The hypothesis test result obtained a significance value of 0.001 < 0.05, indicating that H₀was rejected and H₁ was accepted. In addition, the N-Gain test results showed that the experimental class obtained a score of 77.835 categorized as high and very effective, while the control class obtained a score of 30.681 categorized as moderate and ineffective. Therefore, it can be concluded that the contextual learning approach is effective in improving students’ mathematics learning outcomes on the topic of addition of fractions with different denominators.